Longitudinal and Comparative Analysis of Gut Microbiota of Tunisian Newborns According to Delivery Mode - Hanachi, Mariem; Maghrebi, Olfa; Bichiou, Haifa; Trabelsi, Ferdaous; Bouyahia, Najla Maha; Zhioua, Fethi; Belghith, Meriam; Harigua-Souiai, Emna; Baouendi, Meriem; Guizani-Tabbane, Lamia; Benkahla, Alia; Souiai, Oussema (Frontiers in Microbiology, 2022)
Microbiota colonization is a dynamic process that impacts the health status during one individual’s lifetime. The composition of the gut microbiota of newborns is conditioned by multiple factors, including the delivery mode (DM). Nonetheless, the DM's influence remains uncertain and is still the subject of debate. In this context, the medical indication and the emergency of a cesarean delivery might have led to confounding conclusions regarding the composition and diversity of the neonatal microbiome. Herein, we used high-resolution shotgun sequencing to decipher the composition and dynamics of the gut microbiota composition of Tunisian newborns. Stool samples were collected from 5 Elective Cesarean section (ECS) and 5 vaginally delivered (VD) newborns at each of the following time points: Day0, Day15, and Day30. The ECS and VD newborns showed the same level of bacterial richness and diversity. In addition, the gut microbiota of both groups showed a transition of Both showed a profile dominated by Proteobacteria, Actinobacteria and Firmicutes. However, ECS showed an underrepresentation of Bacteroides and an enrichment of opportunistic pathogenic species of the ESKAPE group; specially from the second week. Besides revealing the intestinal microbiota of Tunisian newborns, this study provides novel insights in the microbiota perturbations caused by elective CS.